Determination of Stability Constants of Ternary Complexes of Lead With Vitamin B5 and Amino Acids (L-Citrulline and Valine) Polarographycally - GUPTA, O.D. (Asian Journal of Chemistry, 2010)
The reduction of Pb(II) in the aqueous solution with amino acids (L-citrulline and valine, vitamin B5) have been investigated at dropping mercury electrode (DME) .The stability constants of Pb-vitamine B5 and Pb-amino acids were measured first by the method of Deford and Humes and that of Pb-amino acids-vitamine B5 have been studied by the method of Shaap and McMasters. The reduction of all the complexes has been found to be reversible and diffusion controlled, involving two electrons in each case. Three types of mixed complexes MXY, MXY2 and MX2Y have been determined and found to be more stable than that of the simple ones. With the help of these data statistical and electrostatic effects have been considered.